Un/covering: Making Disability Identity Legible - Evans, Heather Dawn (Disability Studies Quarterly, 2017)
This article examines one aspect of disability identity among people with non-apparent or "invisible" disabilities: the decision to emphasize, remind others about, or openly acknowledge impairment in social settings. I call this process "un/covering," and situate this concept in the sociological and Disability Studies literature on disability stigma, passing, and covering. Drawing on interviews with people who have acquired a non-apparent impairment through chronic illness or injury, I argue that decisions to un/cover (after a disability disclosure has already been made) play a pivotal role for this group in developing a strong, positive disability identity and making that identity legible to others. Decisions to pass, cover, or un/cover are ongoing decisions that stitch together the fabric of each person's daily life experiences, thus serving as primary mechanisms for identity negotiation and management.